2015
DOI: 10.1007/s00373-014-1515-0
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of the Union-Closed Sets Conjecture

Abstract: We survey the state of the union-closed sets conjecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…be defined as the set of integer vectors contained in the polyhedron defined by Inequalities (2), (4) and (5).…”
Section: Proposition 4 Let a Be A Uc Family Such That ∅ ∈ A And Letmentioning
confidence: 99%
See 2 more Smart Citations
“…be defined as the set of integer vectors contained in the polyhedron defined by Inequalities (2), (4) and (5).…”
Section: Proposition 4 Let a Be A Uc Family Such That ∅ ∈ A And Letmentioning
confidence: 99%
“…Yet, without witnessing first-hand computations for fixed UC families A such that U (A) = [n] and 6 ≤ n ≤ 10, Algorithm 1 may appear fraught with theoretical dangers. 5 However, in practice our method is well-behaved in the described range, and is consequently the currently best available technique for the exact determination of FC-families.…”
Section: Relaxation Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other results have been discovered throughout the years. For a more complete history of the problem, we refer the reader to the following excellent survey [BS14]. Finally, we note that Timothy Gowers recently led a polymath project, FUNC, on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly as a reflection of its general difficulty, Gowers [9] suggested that work on this conjecture could fruitfully be done as a collaborative Polymath project. See [2] for a survey of the literature on the union-closed sets conjecture.…”
Section: Introductionmentioning
confidence: 99%